Purification and preliminary crystallographic analysis of a new Lys49-PLA2 from B-jararacussu - dos Santos, Marcelo L.; Fagundes, Fabio H. R.; Teixeira, Bruno R. F.; Toyama, Marcos H. [UNESP]; Aparicio, Ricardo (Mdpi Ag, 2008)
BjVIII is a new myotoxic Lys49-PLA2 isolated from Bothrops jararacussu venom that exhibits atypical effects on human platelet aggregation. To better understand the mode of action of BjVIII, crystallographic studies were initiated. Two crystal forms were obtained, both containing two molecules in the asymmetric unit (ASU). Synchrotron radiation diffraction data were collected to 2.0 angstrom resolution and 1.9 angstrom resolution for crystals belonging to the space group P2(1)2(1)2(1) (a = 48.4 angstrom, b = 65.3 angstrom, c = 84.3 angstrom) and space group P3(1)21 (a = b = 55.7 angstrom, c = 127.9 angstrom), respectively. Refinement is currently in progress and the refined structures are expected to shed light on the unusual platelet aggregation activity observed for BjVIII.
Keywords: Lys49-PLA2; Bothrops jararacussu; platelet aggregation; phospholipase crystallographic analysis